The Short-Term Efficacy and Safety of iStent Implantation Combined With Cataract Extraction on Lowering The Intraocular Pressure in Patients with Glaucoma: A Pilot Study in Indonesia - Rini Sulastiwaty; Q Syahril (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2021)
Introduction: Minimally invasive glaucoma surgery (MIGS) is continuously being improved after it was first initiated in the early 2000s. This promising method is hoped to fill the gap between medication and traditional surgeries in management of glaucoma.Objective: To evaluate the efficacy and safety of iStents implantation combined with cataract extraction in managing intraocular pressure in glaucoma patients. Methods: We collected data from 6 eyes of 5 patients with POAG and cataract pre-operatively. The extraction of cataract was then performed, combined with second generation iStents implantation. The follow up procedure included the change of intra ocular pressure (IOP), Visual acuity, and the need for IOP lowering Medication at 1 week and 1 month post-operatively. Results: There was a reduction of mean IOP from the baseline, which was 21.33 ± 6.15 to 18.0 ± 6.0 and 18.11 ± 5.57 at 1-week and 1-month following the surgery. The reduction of IOP was also followed by the reduction of medications needed for the patients. The mean visual acuity following the surgery was also increased from the baseline 0.53 ± 0.41 to 0.85 ± 0.17 at 1 – week and 0.91 ± 0.16 at 1 – month. For safety outcomes, there were no major adverse effect nor complication from the procedures after 1 month of follow up. Conclusion: The iStents implantation helped lowering the IOP of patients with glaucoma. It also reduced the need for further IOP lowering medication following the procedure.